The Effect of Training, Human Resources Competence and Innovation on MSMEs Performance in Post Covid-19: Empirical Study of MSMEs in Bengkalis Regency - Ego Muslim; Desmiyawati; Suci Nurulita (LPPM Universitas Terbuka, 2021)
Performance appraisal or measurement is one of the important factors for MSMEs. Besides being used to assess the success of MSMEs, performance measurement can also be used as a basis for determining the reward system, for example, to determine the level of employee salaries and appropriate rewards. This study aims to evaluate the effect of training, human resources competence, and innovation on the performance of MSMEs in Bengkalis Regency post-Covid-19. The population used in this study is MSMEs in Bengkalis Regency, Riau Province. The sample in this study is 100 MSMEs selected using predetermined criteria. The data used in this study is primary data collected using a questionnaire instrument. The sampling method of this study is simple random sampling. The data analysis is performed using a multiple linear regression model with Statistical Product and Service Solution (SPSS) software version 23.0. The results showed that training, human resource competence, and innovation had a significant effect on the performance of MSMEs.